Chemical Weed Control in Greengram (Pltaseolus radiatus L.) Grown in Transitional Plains of the Luni River Basin Area of Rajasthan - Singh, I; Chandawat, M S; Rathore, M S; Chawra, R S (Annals of Arid Zone, 2016)
Short Communication